Investigating the determinants of household energy consumption in Nigeria: insights and implications - Abubakar, Ismaila Rimi; Alola, Andrew Adewale; Bekun, Festus Victor; Onifade, Stephen Taiwo (Springer Nature, 2024)
Background The present study draws motivation from the United Nations Sustainable Development Goals and explores the nexus between access to modern cooking energy sources, responsible energy consumption, climate change mitigation, and economic growth. Using 2018 demographic and health survey data, the study examines the influence of key socioeconomic and demographic factors on household choice of cooking energy in Nigeria. Results The empirical results show that traditional energy sources are dominant among Nigerian households (74.24%) compared to modern energy sources (25.76%). Regarding energy demographics, male-headed households show more usage of modern energy sources (19.86%) compared to female-headed households (5.90%). Regional analysis reveals that the northwest region predominantly uses traditional energy sources (18.60% of the share of total traditional energy sources), while the southwest region shows the greatest usage of modern energy sources (10.52% of the share of total modern energy sources). Binary logistic regression analysis reveals the positive and statistically significant influence of wealth index, education, and geopolitical region on the likelihood of utilizing modern energy sources. Conversely, household size and place of residence indicate an inverse relationship with the likelihood of adopting modern energy sources. Conclusions These findings have important policy implications for energy efficiency, environmental sustainability, and improving the quality of life in Nigeria, which is currently plagued with significant energy poverty, especially in rural communities.
Keywords: SDGs; Cooking fuel; Demographic and health survey; Stratifed sampling technique; Logistic regression analysis; Household energy; Nigeria; fi=Taloustiede|en=Economics|